A224 THE MANITOBA LIVING WITH IBD STUDY: MEDICATION ADHERENCE AND MARS-5 VALIDATION. (26th February 2020) - Stone, J; Witges, K; Shafer, L; Targownik, L E; Lix, L M; Haviva, C; Walker, J; Graff, L A; Vagianos, K; Sargent, M; Bernstein, C N
Abstract: Background: Medication non-adherence in IBD has previously been reported to be quite variable, ranging from 7 to 73%, and is considered to be an important contributor to disease flares. While there is currently no gold standard for medication adherence reporting in IBD, the Medication Adherence Reporting Scale 5 (MARS-5) has frequently been used in this population, but never validated. Aims: This study aimed to analyze medication adherence rates in a cohort of persons with IBD in Manitoba, report predictors of medication non-adherence on self-reported symptoms, and validate the MARS-5 as a medication adherence tool. Methods: 55 subjects were prospectively followed with biweekly online surveys in the Manitoba Living with IBD Study. Subjects not taking any medications for IBD or only taking as needed, missing adherence data and those lost to follow-up were excluded, leaving 112 subjects. Descriptive data on demographics, surgeries, IBD medications, medication adherence, and measures of disease activity utilizing IBDSI-SF scores were collected. Mean annual medication adherence percentage, IBDSI-SF(>14=active for Crohn's, >13=active for UC) and MARS-5 scores were calculated. Logistic regression analysis was performed to determine variables associated with medication adherence and to validate the MARS-5. Results: Mean age was 42.9 years (SD 12.8), with 71.4% being female. Crohn's disease (CD) was diagnosed in 67.9%, with 37.5% having undergone at least one abdominal surgery. 70.5% of patients were on 2 or more IBD medications. Mean IBDSI score was 15.5 and mean MARS-5 score was 22.5. 20 (17.9%) patients reported a mean adherence of <90% across all medications- 18 were oral medication users, 1 was on an infusion biologic and 1 on subcutaneous adalimumab. 10 (9.8%) had adherence <80%, all of which were to oral medications. Multivariate regression analysis revealed only a diagnosis of Crohn's disease (OR 4.62; 95% CI 1.37–15.7; p=0.014 ) to be a predictor of adherence. Disease activity as defined by IBDSI (OR 0.43, 95% CI 0.13–1.45; p=0.139 ) and fecal calprotectin >250ug/L (OR 1.04, 95% CI 0.35–3.11; p=0.724 ), age >55 (OR 2.37, 95% CI 0.65–8.65; p=0.476 ), female sex (OR 0.38, 95% CI 0.097–1.52; p=0.150 ) and stress (OR 0.67, 95% CI 0.19–2.32; p=0.498 ) were not shown to be predictors. MARS-5 was compared to percentage adherence, showing moderate correlation (Pearson r=0.46 ). Logistic regression analysis showed each additional MARS-5 point was associated with a 1.7 times greater odds of >90% adherence. Conclusions: We report a highly adherent Manitoba IBD cohort. A diagnosis of CD was the only predicitor of adherence. MARS-5 showed moderate correlation with mean percentage adherence values, suggesting it is a valid assessment tool for determining medication adherence in an IBD population. Funding Agencies: None